An Integrated LC-ESI-MSn and High Resolution LC-ESI-QTOF Approach for the Identification of Phloroglucinols from Nepalese Hypericum japonicum - Gregorio Peron; Deepak Raj Pant; Shyam Sharan Shrestha; Sangeeta Rajbhandary; Stefano Dall’Acqua (Molecules, 2020)
Phloroglucinols are characteristic constituents of Hypericumjaponicum that are claimed to exert several bioactivities, such as anti-inflammatory, anti-depressant and anti-viral ones. Phloroglucinols are unstable compounds and their synthesis is challenging; thus, isolation from natural sources is still one of the main strategies for obtaining these constituents in purified form. Assessing the presence of phloroglucinols in plant materials can be of interest for compound isolation, and LC-MS approaches afford sensitivity and specificity in this regard. In this work, we combined data from quadrupole-time of flight (QTOF) and ion trap (IT) mass spectrometers in order to assess the presence of the phloroglucinols characteristic of H. japonicum and to elucidate their MS fragmentation pathways. The identified compounds present similar structures bearing the 1,3,5-trihydroxybenzene core with different substitutions, which, in constituents at higher MW, is linked to 3′,3′-dimethyl-6′-oxo-phlorisobutyrophenone by a methylene bridge. Differences in MS2 spectra of the considered phloroglucinols are useful for compound identification and differentiation, and to perform dereplication studies. Overall, the proposed approach could be useful for the analysis of phloroglucinols in H. japonicum and other plant species.